Central Nervous System Involvement in Henoch-Schonlein Purpura in Children and Adolescents. (21st January 2017) - Pacheva, Iliyana H.; Ivanov, Ivan S.; Stefanova, Krastina; Chepisheva, Elena; Chochkova, Lyubov; Grozeva, Dafina; Stoyanova, Angelina; Milenkov, Stojan; Stefanova, Penka; Petrova, Anna
Abstract : Central nervous system (CNS) involvement in Henoch-Schonlein purpura (HSP) is rare but poses diagnostic difficulties. The aim of the study was to establish the frequency of CNS involvement in HSP, to analyze its clinical characteristics and do a literature review. Medical files of patients with HSP admitted at the Department of Pediatrics, Plovdiv, were studied retrospectively for a five-year period (2009–2013). Diagnosis was based on the American College of Rheumatology criteria. Out of 112 children with HSP 1 case (0.9%) had CNS involvement presenting as Posterior Reversible Encephalopathy Syndrome (PRES), which may be a result of CNS vasculitis or arterial hypertension. It was an 8-year-old girl with atypical HSP which started with abdominal pain requiring surgery. On the third day after the operation a transient macular rash and arterial hypertension appeared, followed by visual disturbances, hemiconvulsive epileptic seizures, postictal hemiparesis, and confusion. Head CT showed occipital hypodense lesions and MRT-T2 hyperintense lesion in the left occipital lobe. The patient experienced a second similar episode after 2 weeks when palpable purpura had also appeared. Neurological symptoms and MRI resolved completely. HSP can be an etiological factor for PRES in childhood. Although PRES is a rare complication of HSP, clinicians must be aware of it and avoid diagnostic and therapeutic delays.